2004
DOI: 10.1063/1.1812011
|View full text |Cite
|
Sign up to set email alerts
|

Laminar drag reduction in microchannels using ultrahydrophobic surfaces

Abstract: A series of experiments is presented which demonstrate significant drag reduction for the laminar flow of water through microchannels using hydrophobic surfaces with well-defined micron-sized surface roughness. These ultrahydrophobic surfaces are fabricated from silicon wafers using photolithography and are designed to incorporate precise patterns of microposts and microridges which are made hydrophobic through a chemical reaction with an organosilane. An experimental flow cell is used to measure the pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
667
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 940 publications
(707 citation statements)
references
References 26 publications
33
667
3
4
Order By: Relevance
“…It is safe to assume that in the case of this rough surface, the solid fraction of the spreading lamella was at an intermediate value between that of its smooth and textured counterparts and, therefore, that the value of m decreased monotonically for surfaces exhibiting lower solid fractions in our experiments. A low solid fraction reduces the magnitude of m because the conventional no-slip boundary condition for fluid flow over a solid is no longer valid on an air-trapping surface [36]. On such surfaces, only the solid fraction of the lamella is subject to the no-slip condition (and is hence dragged by the tangential motion of the surface), while the remaining fraction flows over trapped air, experiencing minimal drag, which explains why the tangential velocity of the surface had a diminished effect on the impact behaviour for the rough and textured surfaces tested.…”
Section: Modelling the Splashing Thresholdmentioning
confidence: 99%
“…It is safe to assume that in the case of this rough surface, the solid fraction of the spreading lamella was at an intermediate value between that of its smooth and textured counterparts and, therefore, that the value of m decreased monotonically for surfaces exhibiting lower solid fractions in our experiments. A low solid fraction reduces the magnitude of m because the conventional no-slip boundary condition for fluid flow over a solid is no longer valid on an air-trapping surface [36]. On such surfaces, only the solid fraction of the lamella is subject to the no-slip condition (and is hence dragged by the tangential motion of the surface), while the remaining fraction flows over trapped air, experiencing minimal drag, which explains why the tangential velocity of the surface had a diminished effect on the impact behaviour for the rough and textured surfaces tested.…”
Section: Modelling the Splashing Thresholdmentioning
confidence: 99%
“…In this case the slip length can be based on the change in the shear rate on the upper wall or the change in the pressure drop or mass flow rate (Ou et al 2004;Ou & Rothstein 2005;Govardhan et al 2009) by finding the analytic solution for a velocity profile that gives the same effect with the assumption of a slip length boundary condition on the superhydrophobic walls. In the Couette flow case the resulting slip is equal to the slip length based on the local velocity profile at the wall, since the velocity profile is linear.…”
Section: Slip Length Based On Mean Flow Quantitiesmentioning
confidence: 99%
“…Due to the lower dynamic viscosity of air compared to water the trapped air layer on a superhydrophobic surface has a lubricating effect on the flow over it. Drag reducing properties of superhydrophobic surfaces have been observed experimentally in microfluidic devices (Choi, Westin & Breuer 2003;Ou, Perot & Rothstein 2004;Ou & Rothstein 2005;Joseph et al 2006;Daniello, Waterhouse & Rothstein 2009;Govardhan et al 2009;Tsai et al 2009;Rothstein 2010) and for coated objects, such as hydrofoils (Gotge et al 2005), settling spheres (McHale et al 2009) and cylinders (Muralidhar et al 2011), covering flow regimes from laminar to turbulent. In a stable configuration, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Tretheway and Meinhart [2002] showed that the no-slip boundary condition was valid for a clean hydrophilic microchannel but slip occurred over a hydrophobic surface. Ou et al [2004] demonstrated a significant drag reduction, consequently resulting in slip at a solid-fluid boundary, for laminar flow of water through micron-sized channels with hydrophobic surfaces. Slip increases flow rate of fluid, which can be analytically quantified by introducing a concept of slip length [Ou et al, 2004].…”
Section: Introductionmentioning
confidence: 99%